A Narrative Review: Efficacy and Safety the Used of Corticosteroids as an Adjunct Therapy for Rheumatoid Arthritis - Hendra Herman; Irma Rachma Hanifah; Kamri, Andi Maulana (PT Inovasi Pratama Internasional, 2022)
Rheumatoid Arthritis (RA) is an autoimmune disease characterized by inflammation of the joints. The selection of corticosteroids with broad indications is used as an adjunct therapy because of its anti-inflammatory activity and immune suppression. The research aimed to determine the efficacy and safety profile of corticosteroids in rheumatoid arthritis patients. The method used was a literature review with a narrative review design based on inclusion and exclusion criteria through the PubMed and Google Scholar databases. The results showed that the Prednisone group with varying doses of 5 mg; 6.25 mg; 10 mg gave better efficacy than the placebo group or Methotrexate monotherapy against disease activity with the DAS28 parameter. Prednisone safety was observed from the side effects, hypertension; hyperglycemia and adverse events, headache; reported diarrhea. The review show that the use of Prednisone tab 10 mg/day provided the best efficacy in the first 3 months (p<0.001) with the DAS28 parameter which achieved the greatest clinical remission. The side effects of Prednisone could not be concluded between the effect of dose and the level of drug safety.